An investigation of macroergonomic person factor effect on consulting work system performance - Çetin, Fatma Zehra. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2021., 2021)
Macroergonomics has been one of the signifficant approaches to contribute to design of the systems with human element for well being and system's performance. Previous macroergonomics studies concentrated exclusively on the design and analysis of the manufacturing work systems. On the other hand, the value of adding a macroergonomic approach with all its components to a service work system has received little consideration. This study addresses this gap in the existing literature and investigates the effects of person which is one of the macroergonomics factor on consulting work system performance. Speciffically, study objectives are twofolds: (i) Developing a person factor-related hypothesis model representing consulting work system performance; and (ii) Determine the direct, indirect and total effects of the four person factor elements on the consulting work system performance using the developed hypothesis model. To reach the stated objectives, a person-factor hypothesis model for consulting work system performance was developed. A macroergonomics compatibility questionnaire (MCQ) was created for data gathering from the managerial staff of various consulting companies. To define key 'driver' constructs and estimate the direct, indirect, and total effects, the variance based PLS-SEM technique was performed. The ndings indicated that for higher employee performance, the macroergonomic compatibility of cognitive skills, education and knowledge, psychological characteristics and motivation and needs are signifficant person related elements. Total effects in the hypothesis model revealed that employee performance signi cantly effects organizational performance and service process. In this regard, the developed model may help consulting companies to enhance service quality and stay competitive in today's business world.
Keywords: Human engineering.